2016
DOI: 10.1007/s10815-016-0748-7
|View full text |Cite
|
Sign up to set email alerts
|

Closed vitrification of human oocytes and blastocysts: outcomes from a series of clinical cases

Abstract: Purpose High survival rates and clinical outcomes similar to those from fresh oocytes and blastocysts have been observed with open oocyte vitrification systems. It has been suggested that the extremely fast cooling rates that are only achieved with open systems are necessary for human oocyte and blastocyst vitrification. However, there is a potential risk of introducing contamination with open systems. The aim of this study was to assess whether similar survival and subsequent implantation rates could be achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Since DMSO is the most commonly used as a cryoprotectant for freezing of oocytes and embryos for storage purposes, we propose that it is imperative to understand its biological effects on the developmental competence of mammalian embryos both in vitro and in vivo ; this remains a major concern in toxicological studies. 17 - 19 Recently, Zhou et al demonstrated that DMSO treatment affected the asymmetric division of mouse oocytes. 20 Detrimental effects of DMSO have also been reported in the development of both rat and zebrafish embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Since DMSO is the most commonly used as a cryoprotectant for freezing of oocytes and embryos for storage purposes, we propose that it is imperative to understand its biological effects on the developmental competence of mammalian embryos both in vitro and in vivo ; this remains a major concern in toxicological studies. 17 - 19 Recently, Zhou et al demonstrated that DMSO treatment affected the asymmetric division of mouse oocytes. 20 Detrimental effects of DMSO have also been reported in the development of both rat and zebrafish embryos.…”
Section: Introductionmentioning
confidence: 99%
“…The basic characteristics of the selected literatures are listed on Table 1 . Results of the methodological quality assessment showed that 3 of the prospective studies were of low risk of bias [ 8 , 17 , 22 ], 2 were moderate [ 13 , 16 ] and 3 were of serious risk of bias [ 20 , 21 , 23 ]. The results of the quality assessment of the included retrospective studies were shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding embryo cryopreservation, several studies reported comparable results between open and closed vitrification on survival rates after thawing [ 13 18 ]; while others demonstrated that closed vitrification outperformed the open one [ 19 , 20 ]. For oocytes vitrification, some suggested that ‘open’ was better than ‘closed’ in post-thawing survival rates [ 7 , 8 , 21 ]; others found no statistical differences between these two methods [ 22 , 23 ]. In addition, the rest of the embryologic and clinical outcomes differed from each other according to the studies mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…One clear advantage that IVF centers have over those only involved in long-term sperm banking is in the continuous demonstration of the effectiveness of their procedures. Vitrification procedures are now providing recovery rates in excess of 85 to 90% for both oocytes and blastocysts, 34,35 which in turn translate into successful pregnancies. Performance testing the process of cryopreservation is therefore relatively straightforward since any significant reduction in recovery or pregnancy rate would prompt investigation of conditions during the addition of cryoprotectants, cooling, and storage.…”
Section: Risk and The Quality Of Frozen-thawed Materialsmentioning
confidence: 99%